2021
DOI: 10.24059/olj.v25i2.2232
|View full text |Cite
|
Sign up to set email alerts
|

Designing Educational Videos for University Websites Based on Students’ Preferences

Abstract: Recent developments have seen a significant increase in the number of educational videos being made, mostly for use as a resource in a range of educational levels and different specializations. Indeed, currently, many universities either provide videos as supplementary resources or, indeed, offer entire courses as online learning materials. The qualitative study this paper presents was conducted to answer the following questions: “How have educational videos (lectures/tutorials) published on YouTube affected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
7
1
2
Order By: Relevance
“…The fourth questionnaire result showed that YouTube is not a full recommendation e-learning tool for online learning. This result is different from the previous research that the use of YouTube for an educational videos is good evidence for academic discipline (Alfayez, 2021). Participants positively viewed the use of YouTube in their lessons (Kabooha & Elyas, 2018).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The fourth questionnaire result showed that YouTube is not a full recommendation e-learning tool for online learning. This result is different from the previous research that the use of YouTube for an educational videos is good evidence for academic discipline (Alfayez, 2021). Participants positively viewed the use of YouTube in their lessons (Kabooha & Elyas, 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…There were several previous studies that examined about YouTube as e-learning tool. Alfayez (2021) observed that the use of YouTube for an educational videos is good evidence for academic discipline. Kabooha & Elyas (2018) observed that participants positively viewed the use of YouTube in their lessons.…”
Section: Introductionmentioning
confidence: 99%
“…The frequent occurrence of “professional development” and its connection to “curriculum” and varying student‐centered instructional approaches suggest the pressing needs, challenges or opportunities of supporting faculty in providing effective online instruction (eg, Ó Ceallaigh, 2021 ; Rupnow et al., 2020 ). Regarding technology, many studies investigated how clickers, videos, YouTube and online platforms supported student learning (eg, Alfayez, 2021 ; Chiu, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Alfayez [13] conducted a qualitative research project to answer the following questions: "How have instructional films (lectures/tutorials) broadcast on YouTube influenced university students' studies at both the postgraduate and undergraduate levels?" "Would it be more appropriate to post these types of films on a UW?"…”
Section: Other Countries and Regionsmentioning
confidence: 99%
“…UWs had been well investigated for improvement of usability for all users in general [3,5,8,[10][11][13][14][15][16][17][18][19][20][21][22][23][24], such as students-lectures [4,13,25], people with disabilities [26], and even during the pandemic time [26][27][28][29]. However, there has been no holistic understanding and general trends based on the above literature on UW.…”
Section: Introductionmentioning
confidence: 99%